INOVASI JEMPUT BOLA ADMINISTRASI KEPENDUDUKAN (JEBOL ANDUK) DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Marselus Yollan Lokabora; Noora Fithriana (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: This study used a descriptive qualitative research method with the data sources were primary and secondary data. The data collection was gained through observation, interviews and documentation. The research instrument included the researcher himself, interview guidelines, and field notes. The technique of determining informants used a snowball sampling. While the data validity used triangulation technique and the data analysis techniques included data collection, data presentation and withdrawing conclusions / verification. The results of this study concluded that the service